Oncology clinic-based germline genetic testing for exocrine pancreatic cancer enables timely return of results and unveils low uptake of cascade testing. Issue 8 (23rd September 2021) - Wang, Yifan; Golesworthy, Bryn; Cuggia, Adeline; Domecq, Celine; Chaudhury, Prosanto; Barkun, Jeffrey; Metrakos, Peter; Asselah, Jamil; Bouganim, Nathaniel; Gao, Zu-Hua; Chong, George; Foulkes, William D; et al.
Abstract : Background: Traditional medical genetics models are unable to meet the growing demand for germline genetic testing (GT) in patients with exocrine pancreatic cancer (PC). This study investigates the impact of an ambulatory oncology clinic-based GT model. Methods: From 2012 to 2021, patients with PC were prospectively enrolled and considered for GT. Two chronological cohorts were compared: (1) the preuniversal genetic testing (pre-UGT) cohort, which received GT based on clinical criteria or family history; and (2) the post-UGT cohort, where an 86-gene panel was offered to all patients with PC. Results: Of 847 eligible patients, 735 (86.8%) were enrolled (pre-UGT, n=579; post-UGT, n=156). A higher proportion of the post-UGT cohort received prospective GT (97.4% vs 58.5%, p<0.001). The rate of pathogenic germline alterations (PGA) across both cohorts was 9.9%, with 8.0% of PGAs in PC susceptibility genes. The post-UGT cohort had a higher prevalence of overall PGAs (17.2% vs 6.6%, p<0.001) and PGAs in PC susceptibility genes (11.9% vs 6.3%, p<0.001). The median turnaround time from enrolment to GT report was shorter in the post-UGT cohort (13 days vs 42 days, p<0.001). Probands with a PGA disclosed their GT results to 84% of their first-degree relatives (FDRs). However, only 31% of informed FDRs underwent GT, and the number of new cases per index case was 0.52. Conclusion: A point-of-care GT model is feasible and expedites access to GT for patients with PC. Strategies to increase the uptake of cascade testing are needed to maximise the clinical impact of an oncology clinic-based GT model.